Content analysis of the sexual harassment protocols in 29 Health Services in Chile - Pantoja, Valentina; González, Vivian; Viveros, Gisela; Catalán, Manuel; González, Felipe; Franz, Nicole; Soto-Salazar, Carolina; Valenzuela, Valentina; Jadue, Gabriela; Valencia, Penélope; Harden, Natalia; Crispi, Francisca (Revista Chilena de Salud Pública, 2022)
Introduction: Sexual harassment is a frequent type of gender-based violence that deeply undermines personal integrity and human rights. It can occur in different contexts and even today, health centers are not free from this practice. Currently there are mandatory instructions that establish that all Health Services must have sexual harassment protocols. The objective of this review is to evaluate the sexual harassment protocols of the Chilean Health Services for health personnel. Material and Methods: A content analysis of the 29 sexual harassment protocols of the Chilean Health Services was developed, considering 2015 and 2018 mandatory instructions. Fourteen evaluation items were generated. The content of each protocol was extracted by item, and then categorized quantitatively (very adequate, adequate, insufficient, absent) and a synthesis of its content was made qualitatively. The degree of compliance of each item was described, and a data analysis was carried out. Results: 100% of the protocols of the Health Services were analyzed. Heterogeneity in their quality was evidenced, with important deficiencies in the preventive approach, clarity of the process and reparatory measures. Discussion: The findings suggest a revision of sexual harassment protocols to optimize and homogenize their quality and relevance.